Analisis Tingkat Kesejahteraan Masyarakat Nelayan Ikan Hias Di Desa Rantau Rasau Kecamatan Berbak Kabupaten Tanjung Jabung Timur - Syamsudin Syamsudin; Bambang Kurniawan; Agusriandi Agusriandi (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study aims to find out how the level of welfare of fishermen in Rantau Rasau Village, the number of informants in this study were 2 informants, namely the village government and fishing communities. The type of this research is descriptive qualitative with primary data and secondary data. Data collection techniques in this study used observation, documentation and interview techniques, while for data analysis the researchers used data reduction, data presentation and verification. The results of this study explain the level of welfare of the fishing community in Rantau Rasau Village where there are seven indicators of welfare as and three indicators of welfare have been fulfilled by fishermen in Ranatu Rasau Village, namely: family health, transportation facilities and social participation, from the levels that have been fulfilled there are four indicators of welfare that have not been met, namely: the state of residence, housing facilities, income and consumption and the ease of sending children to school.